2008
DOI: 10.1563/1548-1336-34.6.303
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid and Prostaglandin E2 Influence Human Osteoblast (MG63) Response to Titanium Surface Roughness

Abstract: Prior studies have shown that implant surface roughness affects osteoblast proliferation, differentiation, matrix synthesis, and local factor production. Further, cell response is modulated by systemic factors, such as 1,25(OH)2D3 and estrogen as well as mechanical forces. Based on the fact that peri-implant bone healing occurs in a site containing elevated amounts of prostaglandin E2 (PGE2), the hypothesis of the current study is that PGE2 and arachidonic acid (AA), the substrate used by cyclooxygenase to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Our findings are also at least partially supported by Dean et al, who reported that indomethacin increased ALP expression on micro rough discs in MG63 cells (31). Factors like PGE 2 or indomethacin dose and timing of application in culture have also been proven to be relevant in determining their overall effect, thus indicating that the action of PGE 2 is indeed complex and must be finely tuned (31,35). Moreover, the discovery of isoforms of PGE 2 receptors with distinct expression and effects must be taken into account when interpreting the results reported in the literature (39,40).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are also at least partially supported by Dean et al, who reported that indomethacin increased ALP expression on micro rough discs in MG63 cells (31). Factors like PGE 2 or indomethacin dose and timing of application in culture have also been proven to be relevant in determining their overall effect, thus indicating that the action of PGE 2 is indeed complex and must be finely tuned (31,35). Moreover, the discovery of isoforms of PGE 2 receptors with distinct expression and effects must be taken into account when interpreting the results reported in the literature (39,40).…”
Section: Discussionsupporting
confidence: 90%
“…In their study, Dean et al. () demonstrated that treatment of MG‐63 with 1–100 nM PGE 2 resulted in an increase of TNAP activity when cells were cultured on polished titanium surface and in a decrease of TNAP activity when cells were cultured on rough titanium surface. Considering MG‐63 as a kind of native drug delivery system, the amount of endogenously formed of PGE 2 (~0.85 nM) could be sufficient to cause the decrease of TNAP on both SBA surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…34 demonstrated that PGE 2 could significantly inhibit osteocalcin production by human osteoblasts at concentrations as low as 1 nM 34 . Equivalent concentrations of PGE 2 were also shown to significantly impair ALP activity in human MG63 osteoblast-like cells 35 . More recently, PGE 2 was shown to effectively suppress hBMSC-mediated matrix mineralization 18 .…”
Section: Discussionmentioning
confidence: 92%